Performance-Based Maintenance Contract (PBMC) under Second Bangladesh Rural Transport Improvement Project (RTIP-II): lessons learned and way forward - Siddique, Sajjad Bin (BRAC Univeristy, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2017.